The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1161/hypertensionaha.116.07659
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Eleven Simplified Methods for the Identification of Elevated Blood Pressure in Children and Adolescents

Abstract: The identification of elevated blood pressure (BP) in children and adolescents relies on complex percentile tables. The present study compares the performance of 11 simplified methods for assessing elevated or high BP in children and adolescents using individual-level data from seven countries. Data on BP were available for a total of 58,899 children and adolescents aged 6–17 years from seven national surveys in China, India, Iran, Korea, Poland, Tunisia and the USA. Performance of the simplified methods for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…To improve the detection of pediatric elevated BP, several simplified definitions were developed . Cross‐sectional studies suggested that those simplified definitions had high sensitivities and moderate specificities in comparison with the Fourth Report .…”
Section: Discussionmentioning
confidence: 99%
“…To improve the detection of pediatric elevated BP, several simplified definitions were developed . Cross‐sectional studies suggested that those simplified definitions had high sensitivities and moderate specificities in comparison with the Fourth Report .…”
Section: Discussionmentioning
confidence: 99%
“…Simplified criteria have been proposed to ease such burdens. 18,19 However, these simplified criteria still have concerns, such as lack of data in younger children below age 6 and misclassifications; clinical utility of simplified criteria to guide clinical practice is yet to be established in further studies. 6 As electronic healthcare systems are increasingly used, elevated BP in children can be marked with the age-, sex-, and height-specific percentiles integrated into the electronic systems.…”
Section: O M M E N T a R Ymentioning
confidence: 99%
“…Fifth, the current available national or international standards are age, sex, and height specific, resulting in a large number of cutoff points, which are cumbersome in clinical practice. Simplified criteria have been proposed to ease such burdens . However, these simplified criteria still have concerns, such as lack of data in younger children below age 6 and misclassifications; clinical utility of simplified criteria to guide clinical practice is yet to be established in further studies .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…15, 16 However, these simplified methods are either still difficult to use or have low positive predictive values compared with the complex definition specific for sex, age and height percentiles. 1719 …”
Section: Introductionmentioning
confidence: 99%